Analyses on the infection process of rice virus and the spatiotemporal expression pattern of host defense genes based on a determined-part inoculation approach - Guo, Wei; Li, Chenyang; Zeng, Bo; Li, Jie; Wang, Zhaoyun; Ma, Shuhui; Du, Linlin; Lan, Ying; Sun, Feng; Lu, Chengye; Li, Shuo; Zhou, Yijun; et al. (MDPI, 2022)
Rice viral diseases adversely affect crop yield and quality. Most rice viruses are transmitted through insect vectors. However, the traditional whole-plant inoculation method cannot control the initial inoculation site in rice plants because the insect feeding sites in plants are random. To solve this problem, we established a determined-part inoculation approach in this study that restricted the insect feeding sites to specific parts of the rice plant. Rice stripe virus (RSV) was used as the model virus and was inoculated at the bottom of the stem using our method. Quantitative real-time PCR and Western blot analyses detected RSV only present at the bottom of the Nipponbare (NPB) stem at 1 day post-inoculation (dpi), indicating that our method successfully controlled the inoculation site. With time, RSV gradually moved from the bottom of the stem to the leaf in NPB rice plants, indicating that systemic viral spread can also be monitored using this method. In addition, a cultivar resistant to RSV, Zhendao 88 (ZD88), was inoculated using this method. We found that RSV accumulation in ZD88 was significantly lower than in NPB. Additionally, the expression level of the resistant gene STV11 in ZD88 was highly induced at the initial invasion stage of RSV (1 dpi) at the inoculation site, whereas it remained relatively stable at non-inoculated sites. This finding indicated that STV11 directly responded to RSV invasion to inhibit virus accumulation at the invasion site. We also proved that this approach is suitable for other rice viruses, such as Rice black-streaked dwarf virus (RBSDV). Interestingly, we determined that systemic infection with RSV was faster than that with RBSDV in NPB, which was consistent with findings in field trails. In summary, this approach is suitable for characterizing the viral infection process in rice plants, comparing the local viral accumulation and spread among different cultivars, analyzing the spatiotemporal expression pattern of resistance-associated genes, and monitoring the infection rate for different viruses.